2002
DOI: 10.3310/hta6110
|View full text |Cite
|
Sign up to set email alerts
|

Screening for gestational diabetes: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(96 citation statements)
references
References 108 publications
6
83
1
6
Order By: Relevance
“…While these predictors are in accord with the literature [4,12,32,33], it is of interest that maternal overweight/obesity gave almost no contributing information and was therefore not included in the final model. The first clinical scoring system for GDM prediction, presented by Naylor et al, was based on preconception BMI in addition to maternal age and ethnicity [17].…”
Section: Discussionsupporting
confidence: 63%
“…While these predictors are in accord with the literature [4,12,32,33], it is of interest that maternal overweight/obesity gave almost no contributing information and was therefore not included in the final model. The first clinical scoring system for GDM prediction, presented by Naylor et al, was based on preconception BMI in addition to maternal age and ethnicity [17].…”
Section: Discussionsupporting
confidence: 63%
“…This has shown an improvement of the predictive value of risk factor screening alone when compared with previous studies such as the Health assessment report which showed low sensitivity of 50% -69% and specificity 58% -68% when maternal risk factors alone for prediction of GDM was used [36]. This improvement in the predictive ability of risk factors screening as seen in this study may be explained by the small sample size used in the study.…”
Section: Discussioncontrasting
confidence: 43%
“…However, most national guidelines [13,14] do not recommend it as a screening tool. These guidelines give its low sensitivity for identifying hyperglycaemia/gestational diabetes determined by the glucose tolerance test as a reason for not supporting its use [15]. However, the is a paucity of evidence on the sensitivity and specificity of glycosuria for gestational diabetes screening.…”
Section: Introductionmentioning
confidence: 99%